Mental Health Management Model in Islamic Boarding Schools: Psychological Development Strategy for Students in the Digital Era - Zohriah, Anis; Patimah, Siti; Jubaedi, Ahmad; Marfu, Asep; Nurhayati, Neng (International Journal of Education, Information Technology, and Others, 2025)
The mental health of students in Islamic boarding schools faces increasingly complex challenges in the digital era, but the management model of mental health integrated with Islamic boarding school values is still limited. This study aims to develop a mental health management model in Islamic boarding schools that incorporates a modern psychological approach with Islamic spiritual values in facing the challenges of the digital era. Qualitative research methods, combined with a literature study approach, were applied during the period 2022-2025. This analysis focused on the latest scientific literature regarding the mental health of students, health management models in Islamic educational institutions, and the documentation of best practices in psychological guidance within Islamic boarding schools. The results of the study identified an increase in cases of mental health disorders among students related to the intensity of gadget use, academic pressure, and conflicts between traditional and modern values. The comprehensive mental health management model developed consists of five key components: an early detection system and periodic assessment, an integrated counseling service unit that combines a modern psychological approach with Islamic spiritual values, a tiered digital literacy program, a peer support system, and a referral network and collaboration with professional mental health institutions. The identified implementation strategies include a phased approach, the development of tiered training modules, the integration of programs into the curriculum, and wise use of digital technology. This model bridges the gap between the traditional approach based on religious values and the modern approach based on scientific knowledge and provides an operational framework that can be adapted by various types of Islamic boarding schools according to their characteristics and capacities. The limitation of this study lies in the absence of empirical validation in various types of Islamic boarding schools, so further research is needed to test the effectiveness of the model in various contexts.